The impact of detergents on the tissue decellularization process: a ToF-SIMS study - White, Lisa J.; Taylor, Adam J.; Faulk, Denver M.; Keane, Timothy J.; Saldin, Lindsey T.; Reing, Janet E.; Swinehart, Ilea T.; Turner, Neill J.; Ratner, Buddy D.; Badylak, Stephen F. (Elsevier, 2017)
Biologic scaffolds are derived from mammalian tissues, which must be decellularized to remove cellular antigens that would otherwise incite an adverse immune response. Although widely used clinically, the optimum balance between cell removal and the disruption of matrix architecture and surface ligand landscape remains a considerable challenge. Here we describe the use of time of flight secondary ion mass spectroscopy (ToF-SIMS) to provide sensitive, molecular specific, localized analysis of detergent decellularized biologic scaffolds. We detected residual detergent fragments, specifically from Triton X-100, sodium deoxycholate and sodium dodecyl sulphate (SDS) in decellularized scaffolds; increased SDS concentrations from 0.1% to 1.0% increased both the intensity of SDS fragments and adverse cell outcomes. We also identified cellular remnants, by detecting phosphate and phosphocholine ions in PAA and CHAPS decellularized scaffolds. The present study demonstrates ToF-SIMS is not only a powerful tool for characterization of biologic scaffold surface molecular functionality, but also enables sensitive assessment of decellularization efficacy.